2000
DOI: 10.1136/jnnp.68.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Hedonistic homeostatic dysregulation in patients with Parkinson's disease on dopamine replacement therapies

Abstract: Hedonistic homeostatic dysregulation is a neuropsychological behavioural disorder associated with substance misuse and addiction. The disorder has been recognised as a consequence of dopamine replacement therapy (DRT) in 15 patients with Parkinson's disease. The syndrome typically develops in male patients with early onset Parkinson's disease, and can occur with orally and subcutaneously administered DRT. These patients take increasing quantities of their DRT, despite increasingly severe drug induced dyskinesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
495
4
18

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(526 citation statements)
references
References 30 publications
9
495
4
18
Order By: Relevance
“…PD patients with punding are more likely to be affected by DDS 3,47,48 (56% in the series collected here) and to use rescue medications that are characterized by a rapid effect 3 than nonpunders. DDS is characterized by a compulsive pattern of dopaminergic drug use well beyond that required for motor control in the face of harmful drug-induced sequelae, such as severe dyskinesias and behavioral disturbances (manic behavior).…”
Section: Methods and Review Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…PD patients with punding are more likely to be affected by DDS 3,47,48 (56% in the series collected here) and to use rescue medications that are characterized by a rapid effect 3 than nonpunders. DDS is characterized by a compulsive pattern of dopaminergic drug use well beyond that required for motor control in the face of harmful drug-induced sequelae, such as severe dyskinesias and behavioral disturbances (manic behavior).…”
Section: Methods and Review Criteriamentioning
confidence: 99%
“…DDS is characterized by a compulsive pattern of dopaminergic drug use well beyond that required for motor control in the face of harmful drug-induced sequelae, such as severe dyskinesias and behavioral disturbances (manic behavior). 47 In addition to attenuating the motor symptoms, correcting the DAdeficiency state with DRT may also stimulate central dopaminergic pathways, which are intricately linked to the brain's reward system and are implicated in various states of addiction. In PD, cell loss in dopaminergic neuronal populations giving rise to mesolimbic and mesocortical projections has been nigro-striatal degeneration frontal lobe impairment Figure 3 Proposed pathophysiological relationships between punding, drug-induced stereotypies, dopamine dysregulation syndrome (DDS) and dyskinesias.…”
Section: Methods and Review Criteriamentioning
confidence: 99%
“…A condition that Urologists should be aware of is the ''hedonistic homeostatic disregulation'' syndrome [Giovannoni et al, 2000] which typically develops in male patients who have had early onset PD and been treated for many years with increasing dosages of levodopa. The patient may have severe drug-induced dyskinesia and develop cyclical mood disorder with elements of psychosis.…”
Section: Late Stagesmentioning
confidence: 99%
“…Although several studies, in both animals and humans, have demonstrated beneficial cognitive effects of pro-dopaminergic agents on measures of attention and working memory (Costa et al, 2009;Granon et al, 2000;Mattay et al, 2000;Mehta et al, 2000), there have also been reports of rare but concerning side effects, including induced impulse-control disorders in individuals with no prior history of such difficulties (Dodd et al, 2005;DriverDunckley et al, 2007;Giovannoni et al, 2000;Klos et al, 2005;Madden et al, 2010;McKeon et al, 2007;Munhoz et al, 2009;Potenza et al, 2007;Riba et al, 2008;Voon et al, 2006b;Weintraub et al, 2006). For example, the DA D2/D3 receptor agonist, pramipexole, as well as other DA receptor agonists have been implicated in the emergence of risk-seeking behaviors, such as pathological gambling in multiple case reports and cross-sectional studies in patients with Parkinson's disease (PD) (Bodi et al, 2009;Dodd et al, 2005;Lader, 2008;Pontone et al, 2006;Potenza et al, 2007;Voon et al, 2006aVoon et al, , 2006bWeintraub et al, 2006Weintraub et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%